Virological Features and Clinical Manifestations Associated with Human Metapneumovirus: A New Paramyxovirus Responsible for Acute Respiratory-Tract Infections in All Age Groups - Boivin, Guy; Abed, Yacine; Pelletier, Gilles; Ruel, Louisette; Moisan, Danielle; Côté, Stéphanie; Peret, Teresa C. T.; Erdman, Dean D.; Anderson, Larry J. (The Journal of infectious diseases, 2002)
The virological features and clinical findings associated with the new human metapneumovirus (HMPV) were examined retrospectively in Canadian patients hospitalized for various respiratory conditions since 1993. Thirty-eight previously unidentified respiratory viruses isolated from rhesus monkey kindey (LLC-MK2) cells were found to be positive for HMPV by reverse-transcription polymerase chain reaction, and those strains clustered in 2 phylogenetic groups. Children aged <5 years and elderly subjects aged >65 years represented 35.1% and 45.9% of the HMPV-infected cases, respectively. In hospitalized children, the most frequent diagnoses were pneumonitis (66.7%) and bronchiolitis (58.3%), whereas bronchitis and/or bronchospasm (60%) and pneumonitis (40%) were most commonly seen in elderly subjects. Of the 15 patients with pneumonitis, 4 (26.7%) had immunosuppressive conditions and 6 (40%) were infants aged <15 months. These findings suggest that HMPV can be associated with severe lower-respiratory-tract infections in very young children, the elderly, and immunocompromised patients